Media Sebagai Pelestari Budaya Patriarkhi - Mahfiana, Layyin (Sunan Kalijaga State Islamic University & The Asia Foundation, 2007)
There are two main arguments advanced in this article. Firstly, regarding the image of women perpetuated lry mass media, and secondly why media is not showing gender sensitivity when developing women images. In general mass media portray women in one amongst these five images: women image as a frame, as a column, as an available 'bed', as a saucer and an image of friendship. These images are developed and became popular within a patriarchal culture because men define women as such, and women have no power to disagree. The author proposes that today's women readers must apply more critical view in reading and analyzing the content of mass media, especially with regard to women's images.